Der einfluss vom winter 1978/1979 auf verschiedene haussperlings-populationen - Heij, Cornelis Johannes; Moeliker, Cornelis W.; Visser, S. (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In general House Sparrows "Passer domesticus" live rather well through severe winters in the Netherlands. It is interesting to find that in the severe winter of 1978-1979, during which a combination of strong winds, glazed frost and fine snow covered the feedingsites and roosts with a thick layer of frozen snow, the number of House Sparrows in Leeuwarden (North-Netherlands) diminished by 50%. In Rotterdam (South-West Netherlands) where there was less wind, glazed frost and snow, there was no notably higher mortality during that winter.
Keywords: wróblowe; ornitologia